ANALYSIS OF VISITOR INTEREST IN THE MUSEUM PUSAKA NIAS AS A NATURAL TOURIST ATTRACTION IN 2023/2024 - Waruwu, Fanni Apriani; Harefa, Trisman; Zebua, Elwin Piarawan; Zega, Riswan (FKIP Unismuh Makassar, 2024)
Indonesia is a country that has a variety of cultures and historical heritage from various tribes, cultures, religions, races, as well as heritage from regions in the Indonesian archipelago. This cultural diversity has the potential to be used as cultural tourism by introducing the culture of a region or country. The Nias Islands have cultural tourism at the Museum Pusaka Nias. This research aimed to find out how interested visitors are in the services at the Museum Pusaka Nias, to find out what makes visitors interested in visiting the Museum Pusaka Nias dan to find out the factors that influence visitors interest in the Museum Pusaka Nias by using a qualitative approach. Data collection techniques done through observation, interviews and documentation visitors. The data collected were analyzed to identify themes and factors that influenced visitors’ interest, including personal experiences, knowledge of Nias culture, and expectations of tourist attractions. The research results showed that visitors interests is influenced by various factors, including motivation to learn about Nias culture, the expected experience, and the quality of services provided by the museum. Visitors have a higher interest in animal viewing and recreational activities as well as learning about culture compared to other aspects offered by museums. Factors such as natural beauty, quality of recreational experiences, and a calm atmosphere are the main attractions. Visitors also expressed a desire for better programs, suggesting that the museum could increase its appeal by offering more interactive and nature-oriented experiences. The feeling of joy that when you visit something is in line with your expectations, this will lead to visitors’ satisfaction. It is hoped that this research can provide recommendations for museum managers in improving tourist attractions and visitor experiences.